2013
DOI: 10.1155/2013/305124
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tetracycline in Pharmaceutical Preparation by Molecular and Atomic Absorption Spectrophotometry and High Performance Liquid Chromatography via Complex Formation with Au(III) and Hg(II) Ions in Solutions

Abstract: UV-visible and atomic spectrophotometry and HPLC techniques were applied for the determination of tetracycline (TC) in pharmaceutical preparations via complexation of the drug with Au(III) and Hg(II) ions in solutions. The mole ratio of TC to metal ions was 1 : 1. Maximum peak absorption at λ 425 and 320 nm for the two ions, respectively, was optimized at heating temperature 75°C for 15 minutes at pH = 4 followed by the extraction with ethyl acetate. The percentage of extraction and stability constants for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In agreement with literature (Abdel-Ghani et al, 2016;Abdulghani et al, 2013), TC showed a characteristic UV-Vis absorption spectrum with two main absorption bands in the UV region, corresponding to 𝜋→𝜋 * transitions. These bands can be considered diagnostic for spectrophotometrically following the TC removal, by the pomace, from water.…”
Section: Adsorption Of Tc From Water By Op and Hybrid Ch/op Adsorbentssupporting
confidence: 92%
“…In agreement with literature (Abdel-Ghani et al, 2016;Abdulghani et al, 2013), TC showed a characteristic UV-Vis absorption spectrum with two main absorption bands in the UV region, corresponding to 𝜋→𝜋 * transitions. These bands can be considered diagnostic for spectrophotometrically following the TC removal, by the pomace, from water.…”
Section: Adsorption Of Tc From Water By Op and Hybrid Ch/op Adsorbentssupporting
confidence: 92%
“…The FTIR spectrum of tetracycline shows the characteristic peak at 1660 cm −1 corresponding to the amide carbonyl group. The appearance of a doublet at 1601 cm −1 and 1610 cm −1 accounted for the N—H bending frequency, with the N—H band appending with the O—H band at 3300–3313 cm −1 [31] , [32] . The AVE spectrum exhibited the band at 3344 cm −1 , attributed to the N—H stretching frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The assay of tetracycline in single and multicomponent dosage forms was proposed to carry out using HPLC by isocratic elution with the mixture of acetonitrile and acetate buffer solution as the mobile phase after complexation with metals (Abdulghani et al, 2013), by gradient mode using 0,1% phosphoric acid and acetonitrile (Hussien, 2014) or an acetonitrile/ammonium dihydrogen orthophosphate (pH 2.2) as a mobile phase (Pelia, 2012). For the determination of tetracycline impurity in semisolid medicinal forms, the HPLC method with isocratic elution and a mobile phase consisting of acetonitrile-methanol-80 mM dipotassium phosphate (pH 7.5) was proposed (Giugiu, 2013).…”
Section: Methods Developmentmentioning
confidence: 99%